2013
DOI: 10.1097/gme.0b013e3182831ee4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypocaloric diet, low-intensity resistance exercise with slow movement, or both on aortic hemodynamics and muscle mass in obese postmenopausal women

Abstract: Our findings suggest that diet-induced weight loss may reduce cardiovascular risk by improving SEVR via HR and aortic pulse pressure reductions in obese postmenopausal women. LIRET prevents ASM loss associated with hypocaloric diet but has no additive effects on aortic hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Accordingly, it is reasonable to suppose that the resistance training component of combined training may limit, to a certain degree, the improvement in arterial distensibility. In this regard, previous studies assessing the effect of resistance training programs found either increased [56][57][58] or unaltered [19][20][21][22][23][24] arterial stiffness following the intervention. Interestingly, resistance exercise, despite being associated with disproportionate increases in blood pressure during exercise [16,17], result in decreased blood pressure as a training adaptation [19,23,59], which could favor a decrease in PWV.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Accordingly, it is reasonable to suppose that the resistance training component of combined training may limit, to a certain degree, the improvement in arterial distensibility. In this regard, previous studies assessing the effect of resistance training programs found either increased [56][57][58] or unaltered [19][20][21][22][23][24] arterial stiffness following the intervention. Interestingly, resistance exercise, despite being associated with disproportionate increases in blood pressure during exercise [16,17], result in decreased blood pressure as a training adaptation [19,23,59], which could favor a decrease in PWV.…”
Section: Discussionmentioning
confidence: 83%
“…Arterial remodeling, decreased sympathetic tonus, enhanced endothelial function and improved profile of circulating factors have been suggested as changes underlying the beneficial impact of aerobic exercise training on arterial distensibility [8,13,14]. In contrast, resistance exercise training, which is associated with increased blood pressure that exceeds that expected due to oxygen requirements during exercise and sympathetic activation [15][16][17], does not appear to reduce arterial stiffness [18][19][20][21][22][23][24]. On the other hand, resistance training induces gains in strength and lean body mass, as well as greater increases in bone density compared with aerobic training [25,26].…”
Section: Introductionmentioning
confidence: 95%
“…1,3,4,21,22 We observed that WBV training decreased ankle SBP by 24 mm Hg only in women with high ankle SBP. 24,25 Because both ankle SBP and brachial SBP decreased in the WBV-high group, ABI was not significantly affected (j0.05). This ankle SBP normalization may be clinically important as cardiovascular events are reduced by approximately twofold in individuals with normal ankle SBP compared with those with high ankle SBP.…”
Section: Discussionmentioning
confidence: 96%
“…26 and Figueroa et al . 27 have suggested a reduction in central pressures with RT in older adults and postmenopausal women, respectively. The improvement in central pressure in the present study may be attributed to a decrease in peripheral vascular resistance, as suggested by an accompanied decrease in P2 (defined as the reflected pressure wave that augments the incident wave amplitude).…”
Section: Discussionmentioning
confidence: 99%